Wireless Information-Theoretic Security in an Outdoor Topology with Obstacles: Theoretical Analysis and Experimental Measurements. (29th August 2010) - Chrysikos, Theofilos; Dagiuklas, Tasos; Kotsopoulos, Stavros
Abstract : This paper presents a Wireless Information-Theoretic Security (WITS) scheme, which has been recently introduced as a robust physical layer-based security solution, especially for infrastructureless networks. An autonomic network of moving users was implemented via 802.11n nodes of an ad hoc network for an outdoor topology with obstacles. Obstructed-Line-of-Sight (OLOS) and Non-Line-of-Sight (NLOS) propagation scenarios were examined. Low-speed user movement was considered, so that Doppler spread could be discarded. A transmitter and a legitimate receiver exchanged information in the presence of a moving eavesdropper. Average Signal-to-Noise Ratio (SNR) values were acquired for both the main and the wiretap channel, and the Probability of Nonzero Secrecy Capacity was calculated based on theoretical formula. Experimental results validate theoretical findings stressing the importance of user location and mobility schemes on the robustness of Wireless Information-Theoretic Security and call for further theoretical analysis.